2012
DOI: 10.1016/s1995-7645(12)60162-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and cytoprotective properties of Hyptis suaveolens against oxidative stress–induced damage by CCl4 and H2O2

Abstract: This study shows that H. suaveolens methanol extract can be proposed to protect the liver against CCl(4)-induced oxidative damage in rats and protect the cells against H(2)O(2)-induced oxidative damage in HepG(2) cells. The hepatoprotective and cytoprotective effects might be correlated with its antioxidant and free radical scavenger effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…In the same aspect, Park et al concluded that fucoidan applies anti-inflammatory effects by inhibiting the expression of pro-inflammatory cytokines in vitro and in vivo, together with a restricted antibacterial effect in vivo. Furthermore, fucoidan enhanced the production of pro-inflammatory cytokines, IL-6, IL-8 and TNF-α in human neutrophil and delay neutrophil apoptosis [17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…In the same aspect, Park et al concluded that fucoidan applies anti-inflammatory effects by inhibiting the expression of pro-inflammatory cytokines in vitro and in vivo, together with a restricted antibacterial effect in vivo. Furthermore, fucoidan enhanced the production of pro-inflammatory cytokines, IL-6, IL-8 and TNF-α in human neutrophil and delay neutrophil apoptosis [17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…GST can catalyze the nucleophilic attack of some harmful substances through decreasing glutathione (GSH) level (Kao et al, 2010). MDA, an end-product of lipid hydroperoxide (LPO), is usually used as an indicator of oxidative stress (Ghaffari et al, 2012;Yang et al, 2010). SOD can protect free radical injury by converting O 2− to hydrogen peroxide (H 2 O 2 ) (Jagetia and Reddy, 2005).…”
Section: Discussionmentioning
confidence: 99%
“… 1st group: control group was given corn oil 1 mL/kg, p.o. 2nd group: CCl 4 group was given a single dose of CCl 4 (1 mL/kg, 1:1 mixture with corn oil, p.o.) 3rd, 4th and 5th groups were given DFO (75, 150 and 300 mg/kg, i.p., respectively) daily for 3 days starting 1 hour after CCl 4 .…”
Section: Methodsmentioning
confidence: 99%